Pedido incontroverso: sentença parcial de mérito ou tutela antecipada? e as mudanças com o novo CPC - Pais, Clarissa Castello Novo (2016)
The objective of this study is the legal nature of uncontroversial request of the Civil Procedure Code of 1973 and the changes brought to the New Code of 2015. Reports the concept of request and its species, in particular the meaning of the word "incontrovertible" in our procedural system. Approach the Institute of injunctive relief, the appropriate recourse in the face of the decision anticipates a decision and the new definition of provisional decision of urgency and evidence brought by the Civil Procedure Code of 2015. It presents the legal concept of judgment, their doctrinal classification and examines whether or not partial award of merit in the Code of Procedure of 1973 and the introduction of the institute by the Civil Procedure Law of 2015. it analyzes the controversy in 1973 Procedural system in relation to the uncontroversial request if partial award of merit or injunctive relief and differences in doctrine and case law in this regard and the prevalence for injunctive relief before the legislative choice to include the institute in the chapter of injunctive relief. Introduces the new system brought by the Civil Procedure Code of 2015 on the possibility of partial merit sentences, the framework of uncontroversial request in this chapter and the differences with the new Institute of evidence decision